Evaluating effectiveness of BIM application in Construction Projects (International Journal of Engineering and Computer Science, 2015)
The purpose of this paper is to evaluate the effectiveness of Building Information Modeling (BIM) as method of quantity estimation versus conventional methods. A case study of a residential tower situated in Mumbai is taken into consideration for the comparative analysis. The methodology to be used consists of three stages; model creation, scheduling, and cost estimation with the help of BIM tool. The difference will be then compared between conventional method of estimation and BIM based one with regard to time, accuracy, ease in access and future scope. It is to be noted that BIM has gained popularity in recent times and is also mandated in international projects. The results of the analysis shall be useful in understanding the effectiveness of the tool and to explore innovative means of application of BIM in projects.